Pengaruh Baliho Terhadap Partisipasi Politik Generasi Z - Meiziya Asira Deliyanti; Dinda Arviana; Daniello Rudolf; Isnaini Nurdiah; Muhammad Rafi; Yadi Ruyadi; Fajar Nugraha Asyahidda (PT Polstac Repositori Riset, 2026)
This study aims to identify and fill the existing literature gap regarding the information that only social media can influence the political participation of generation Z, but in reality, billboards can be an effective way to become an integrative and effective communication strategy in reaching generation Z. Billboards are one of the tools to explain the activities of politicians to the public. This study uses a quantitative approach with a survey method. The data collection technique itself is carried out by distributing questionnaires through social media and non-random sampling techniques because there are certain criteria to be achieved in this study, namely generation Z. The results of this study indicate that there is an influence of billboards on the political participation of generation Z in addition to increasing political awareness, especially in the candidate introduction stage. Social media with generation Z is something that cannot be separated so that when there is an interesting billboard, generation Z will upload it to X or Instagram so that this can be more highlighted billboards to raise political awareness. But of course there are weaknesses and strengths, namely the limited public space aspect but can increase popularity.